EFFECTS OF THE SUBSIDIZED STUDENTS’ LOAN ON UNIVERSITY ENROLMENT IN GHANA (Journal of Science and Technology, 2016)
This paper examines the effect of the subsidized students’ loan on university enrolment in Ghana between 1988-2008 using the autoregressive distributed lag (ARDL) framework. It was discovered that the subsidized student loan had positive and significant impact on university en- rolment.  Per capita gross domestic product (GDP) was also found to have a significant and posi- tive impact on enrolment. No evidence was found that future earnings and foregone earnings influenced enrolment decisions. The findings have very important policy implications for Ghana, for example additional policies aimed at improving the students’ loan scheme will have positive impact on both accessibility and efficiency in the university education system.